Նորահայտ մի փաստաթուղթ Շուշիում ավետարանական քարոզիչների գործունեության մասին - Կիրակոսյան, Հասմիկ (Մատենադարան)
In the folder “Shushi” of the archives of the Monastery of the Holy Savior in New Julfa, one can find a document about the activities of the Evangelical Missionary Society of Basel based in Shushi in 1823–1830. The letter is written in Classical Armenian by August Dittrich, a German Evangelical pastor. Dittrich asks Armenian priests to review his Eastern Armenian translation of the Gospel of Matthew, which is attached to the letter, and compare it with the Classical Armenian version. The priest also asks the Catholicos of All Armenians for support and permission to print his manuscript. This unique document provides further information on the linguistic practices of the Evangelical pastors and missionaries based in Shushi, their printing activities and especially their role in the development and dissemination of the Eastern Armenian secular language. В папке «Шуши» архива Храма Святого Всеспасителя Новой Джульфы обнаружен документ о деятельности Базельского евангелического миссионерского общества в Шуши (1823-1830 гг). Письмо написано на грабаре (классическом армянском) немецким евангельским пастором Августом Диттрихом. Диттрих просил армянских священников просмотреть его восточноармянский перевод Евангелия от Матфея, приложенный к письму, и сравнить его с классической армянской версией. Пастор также просил поддержки и разрешения у Католикоса Всех Армян издать рукопись. В документе, содержится дополнительная информация о языковой практике шушинских евангелических пасторов и миссионеров, их издательской деятельности и, в частности, их роли в развитии и распространении восточноармянского языка.
Keywords: Տպագրություն; Արխիվային նյութեր